Kemas Ulang Informasi Sayur Bayam Merah - Mardahlia, Mardahlia; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
In this paper discussed about Red Spinach Information Repackaging. Writing paper aims to describe Red Spinach Spinach Information Package with the aim to facilitate in retrieving information about Red Spinach found in Indonesia. The method of writing this paper is using descriptive method with data collection techniques of literature study. Based on analyzing the data, it can be concluded that Red Spinach Spinach from the leaves to the roots produces many benefits that have a function to maintain health as an enhancer of kidney work, cure various diseases and digestion. In the process of Red Spinach Spinach Information Package required stages as follows: (a) identification of user needs, (b) Collection of information and selection of information resources, (c) packing information, (d) determining audience goals, packaging forms, and making (F) determining the way and system of disseminating the ready-made information packing, (g) transferring the information in printed form, (h) determining the strategy for finding the types of information sources that can help find the information needed, Distribute, disseminate, disseminate, market the packaging of information by means of promotion and user education. Delivering packaged information packets and information sheets to users.Keywords: information repackaging, red spinach, benefits red spinach